Learning Engagement of Adult Females in Remote Physical Fitness Program Through Mobile App Intervention - Ganguly, Ranita; Rathee, N. K.; Rathee, Vikramjit S. (European Scientific Journal, ESJ, 2023)
The use of digital devices such as laptops, personal digital assistants, and mobile phones as learning tools has gained prominence in formal education, generating increased research interest in potential growth areas. According to Jeong and So (2020), there seems to be inadequate empirical evidence from extensive research to support its learning effectiveness in the fitness domain, especially among women who have been underrepresented in economically stressed areas. One of the several explanations for this disparity is the failure to consider women’s intersecting cultural identities or potential for social impact. This paper focuses on addressing this issue by conducting a qualitative study. It involves a focus group comprising 15 adult females aged 24 and above. The primary objective is to assess how virtual learning influences the learning perception of adult female learners at a yoga and fitness studio. Interactive self-paced mobile-assisted learning modules were facilitated through the use of mobile phones. An open-ended questionnaire was designed using online resources for primary data collection. The findings were derived by cross-referencing data collected from recordings, interviews, and questionnaires. The study revealed that participating in online fitness classes could enhance women’s involvement in fitness-related activities.